POLITIK HUKUM JUDICIAL REVIEW DI INDONESIA - Kartono Kartono (Jurnal Dinamika Hukum, 2011)
Although Indonesia judicial review system is not opens the possibility of regulations review under the act against the constitution, das sollen pracitically these conditions may still occur. From political of law the legal authority of constitutional court should be able to put the interests of citizens rights that are based on the principles of recognition, guarantees, protection and legal certainty of a fair and equal treatment before the law. Given that changes in the constitution can not be done easily, then the judicial review in UUD 1945 should not be formulated too limitedly that restricting the organic law to complete and explore the authority that is adaptable to any concrete problem. Keywords: politics of law, constitutional court, UUD 1945, limitedly.